Undercooling studies on dispersed bismuth droplets - Chaubey S.; Singh V.; Ramachandrarao P. (My University, 2025)
In the zinc-bismuth system, a monotectic reaction occurs at 689 K and 0·6 at.% Bi composition. Rapid solidification of the as-cast monotectic alloy led to a micromorphology in which bismuth was uniformly and bimodally distributed as small droplets in the zinc matrix. Statistical analysis of the electron micrographs obtained from different transparent regions of the foils revealed that the size of most of the droplets was about 6 nm. These droplets undercooled by 132 K. An analysis of the nucleation rate measurements shows that the activation energy barrier to nucleation is of the order of 39·8 kcal/mol at the maximum undercooling. © 1987 Indian Academy of Sciences.